Serum Tumor Markers Combined With Clinicopathological Characteristics for Predicting MMR and KRAS Status in 2279 Chinese Colorectal Cancer Patients: A Retrospective Analysis - Zhao, Ning; Cao, Yinghao; Yang, Jia; Li, Hang; Wu, Ke; Wang, Jiliang; Peng, Tao; Cai, Kailin (Frontiers in Oncology, 2021)
Although serum tumour markers (STMs), clinicopathological characteristics and the status of KRAS and MMR play an important role in optimizing the treatment and improving the prognosis of colorectal cancer, their interrelationships remain largely unknown. A retrospective analysis of 2279 patients who underwent KRAS and MMR status testing and STM measurements prior to treatment over the past four years was conducted. Of the 784 patients tested for KRAS and 2279 patients tested for MMR status, KRAS mutations and dMMR were identified in 276 patients (35.20%) and 177 patients (7.77%), respectively. Logistic regression analysis demonstrated that right colon location, well and moderate differentiation and negative CA19-9 were independent predictors for KRAS mutations. The ROC curve yielded an AUC of 0.609 for the combination of the three factors. Age < 65 was an independent predictive factor for dMMR, along with tumour size > 4.6 cm, right colon, poor differentiation, harvested lymph nodes ≥ 22, no lymph node metastasis, no perineural invasion, negative CEA and positive CA72-4. When the nine criteria were used together, the AUC was 0.849. In summary, both STMs and clinicopathological characteristics were found to be significantly associated with the status of KRAS and MMR. The combination of these two factors possessed a strong predictive power for targeted genes among CRC patients.